The Influence of Financial Literacy, Financial Inclusion, and Digital Technology on the Financial Performance of MSMEs in the Digital Economy Era - Muh. Nur; David Christian Engelbert Lisapaly; Ami Nurhayati; Dwi Urip Wardoyo; Awaluddin (SAJMR : Southeast Asian Journal of Management and Research, 2026)
This study aims to analyze the influence of financial literacy, financial inclusion, and digital technology on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in the digital economy era. This research employs a Systematic Literature Review (SLR) approach using the PRISMA framework to identify, evaluate, and synthesize relevant studies published between 2019 and 2025. A total of 30 selected journal articles from Scopus-indexed and SINTA-accredited sources were analyzed. The findings indicate that financial literacy significantly improves financial decision-making and business sustainability, financial inclusion enhances access to formal financial services and funding opportunities, and digital technology adoption increases operational efficiency and market expansion. Furthermore, the integration of these three variables provides a stronger and more sustainable impact on MSMEs’ financial performance. This study contributes to the development of strategies for strengthening MSMEs in the digital economy through financial capability and digital transformation